2013
DOI: 10.1111/iere.12024
|View full text |Cite
|
Sign up to set email alerts
|

Income Redistribution and Public Good Provision: An Experiment

Abstract: We experimentally investigate the impact of income redistribution on voluntary contributions by groups of four subjects. We compare equalizing and unequalizing redistribution. Our data are consistent with the neutrality theorem: Redistribution does not affect the amount of voluntarily provided public good at the group level. However, at the individual level, subjects tend to underadjust with respect to the Nash prediction. We also observe an insignificant adjustment asymmetry between the poor and the rich: Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…To fill this gap in the literature, our study investigates whether and how inequalities in endowments affect contribution levels, without making reference to redistribution as in Maurice et al (2013). We present a (linear) VCM experiment, in which we compare, in a between-subject design, contributions under a symmetric, weakly asymmetric and strongly asymmetric allocation of endowments among four players with respective initial Gini coefficients of 0.000, 0.125, and 0.350.…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap in the literature, our study investigates whether and how inequalities in endowments affect contribution levels, without making reference to redistribution as in Maurice et al (2013). We present a (linear) VCM experiment, in which we compare, in a between-subject design, contributions under a symmetric, weakly asymmetric and strongly asymmetric allocation of endowments among four players with respective initial Gini coefficients of 0.000, 0.125, and 0.350.…”
Section: Introductionmentioning
confidence: 99%
“…The neutrality prediction, i.e. a small unequalizing or equalizing redistribution has no effect on group contribution -was also reported by Maurice et al (2013) who implemented a real income redistribution in their experiment. Subjects played a public good game in two consecutive sequences of 10 rounds, with two different endowment distributions: equal versus unequal (or unequal versus equal).…”
Section: Previous Experimentsmentioning
confidence: 60%
“…public goods games when their endowments are heterogeneous (e.g., Buckley and Croson 2006, Chan et al 1996, Cherry et al 2005, Maurice et al 2013.…”
Section: Collectively Selected Under the Equal Voting Rule The Subjementioning
confidence: 99%
“…Third, a rich experimental literature has found that in situations where their resources are unbalanced, those vested with larger (smaller) resources behave more (less) selfishly (e.g., Buckley and Croson 2006, Chan et al 1996, Cherry et al 2005, Maurice et al 2013. This tension between the higher and lesser endowed members may be severe enough for them to collectively choose a more competitive environment if there is such an opportunity.…”
Section: Introductionmentioning
confidence: 99%